Finnish Teachers' Perspectives on Caring and Meaningful School Development Work - Maarit Hosio; Lauri Heikonen; Arto Kallioniemi; Raisa Ahtiainen (MDPI AG, 2023)
A variety of new policy requirements set for learning and teaching affect the work in schools. The local context in which a school is located forms the grounds for school-level policy adjustments and development work. Caring is a common pedagogical concept and depending on the context its interpretation and meaning varies. Teachers can express their caring attitude in their interactions with students and other teachers. We investigated teachers' perceptions of school development and elements that encourage and motivate teachers to engage in school development work. We also studied caring as one feature in the descriptions related to the work cultures of the schools. The data were teacher group interviews (N = 10) in five different Finnish comprehensive schools located in five different municipalities. In total, 44 teachers participated in the study. We used conventional content analysis allowing a data-driven descriptive approach to the material. The data were thematized and classified into categories concerning the aspects of development work. The categories were further examined to analyze caring. The analysis resulted in finding categories concerning meaningful school development and prerequisites to development that reflected and were aimed at the caring elements in the work culture.